Exploring spatial differences in the risk of child stunting: Evidence from a South African national panel survey. (January 2019) - Otterbach, Steffen; Rogan, Michael
Abstract: South Africa is one of only a handful of countries in which the prevalence of child stunting actually increased during the period (2000–2015) in which global progress towards child health was being monitored. One section of the literature suggests that stunting is a largely rural phenomenon in South Africa which is explained by high rates of poverty, poor living conditions and a low quality and monotonous diet. Another section, however, suggests that highly processed foods available in expanding retail chains have been contributing to a low quality diet across the country, but particularly in poor urban households. To examine these claims about spatial differences in stunting, we use nationally representative longitudinal data (2008–2014) to measure stunting among South African children and adolescents aged 0–19, with particular attention to the determinants of stunting and how its prevalence differs between urban and rural areas. The results suggest that, first, stunting has a strong spatial component in South Africa but that this can be explained, in large part, by observable factors such as household income, living conditions, and access to basic services. Second, subsistence farming has a significant protective role with respect to stunting, even after controlling for household resources and living conditions. Overall, the results suggest that more attention should be paid to low-quality food and 'food systems' as drivers of stunting in both rural and urban areas of a middle-income country such as South Africa. Highlights: Nationally representative data to determine prevalence and correlates of stunting. Conditional on household income, subsistence farming decreases the risk of stunting. Controls for living conditions explain the higher stunting risk in rural households. Evidence of height catch-up after 1000 days. Empirical evidence supporting access to basic services, clean water, and sanitation to address child stunting.